Evaluation of the Growth, Obstacles, and Challenges of E-Money During the COVID-19 Pandemic - Vinanti, Siona; Budy Widjaja Subali, Stefanus; Hastjarja Kustijana B., Dwi; Benny Kusuma, Yoseph (KnE Social Sciences, 2024)
During the COVID-19 pandemic in 2020, electronic money (e-money) was a valuable opportunity as a means of payment. This article used empirical research on millennials to evaluate the growth, barriers and challenges of e-money as a new payment tool in Indonesia. Data collection was conducted through interviews with two e-money issuer executives and 23 millennial e-money customers. Using qualitative methods, the study concluded that the development strategy for e-money was to create innovations that can offer users more security. Increased promotions and cashback at affiliated stores with issued products are also the most popular development strategies for customers. Restrictions on e-money customers included security issues, limited merchants, unstable provider networks, and social-cultural factors (the habit of using traditional cash payment methods). The challenge for e-money issuers was competitors with similar products. Keywords: e-money, payment tool, green finance, COVID-19